Reproducibility of superhydrophobic and oleophobic polymeric micro surface topographies. (21st October 2020) - Baldelli, Alberto; Bschaden, Ben; Amirfazli, Alidad; Sameoto, Dan
Abstract: Micro-structured surfaces can provide useful material properties, such as repellency to water, oil, or alcohols. Multiple polymers were investigated based on micro molding replication fidelity of repellent structures using both advancing and receding contact angle measurements. Five different polymers (Loctite 3525, ST-1060, TC-854, TC-8740, and Teflon AF) were chosen based on a range of durometers, for each of which, a recommended curing process was presented. These polymers were micro-structured via a one-step replica molding to create mushroom shaped fibers with overhanging caps. Teflon AF, a low surface energy polymer, produced innovative superhydrophobic as well as oleophobic Micro Surface Topographies (MSTs). Advancing contact angles (CAs) of these microstructures were 166 ± 4.2, 151 ± 2.9, and 119 ± 2.2 when in contact with a water, ethylene, and olive oil droplet respectively. The highest reproducibility was achieved by using a curing procedure of 100 °C for 2 h. However, even in these conditions, 35% of MSTs were not fully reproduced. ST-1060 was considered a good alternative to Teflon AF since, even after five uses of the same casting mold, the advancing CAs decreased less than 2% when in contact with any liquid tested. Polymeric MSTs resistance to an external force was also examined using a gyratory shaker suggesting that softer materials, such as ST-1060, were required to survive exposure to environmental conditions.